ANALISIS USAHA DAN STRATEGI PENGEMBANGAN AGROINDUSTRI MANISAN PALA DI KELURAHAN AERMADIDI KABUPATEN MINAHASA UTARA (STUDI KASUS DI UD. MURNI) - Chelsy Mea; Tommy F. Lolowang; Benu L.S. Olfie; Ribka M. Kumaat (COCOS, 2014)
AbstractThe objective of this research is to calculate cost, revenue and profit and to know thedevelopment strategy of UD Murni candied nutmeg agroindustry. This study is conductedfrom to May-September 2013, the source of the data in this study were obtained from primarydata through observation and interviews taken directly to the business owner and head of theDepartment of Industry and Trade Industrial North Minahasa Regency. Methods of dataanalysis in this study is adescriptive analysis using SWOT analysis.The research result showed that UD Murni Fixed Cost was Rp. 26 043 while thevariable cost of Rp. 2.31765. UD Murni revenue was Rp. 11.975.000. Therefore profits forproducers of candied nutmeg was Rp. 9,631,307 week or one-time production. The candiednutmeg development strategies through SWOT matrix were: maintaining and expandingmarketing strategies by using technological developments, cooperating with businesspartnerships, improve the quality of products according to consumer tastes, promoting the useof technology as a medium, using technology to get information, and packaging products thatmore attractive than similar products.To develop the business it was needed a quality improvement both in quality productsand services so that consumers are satisfied with the products offered, establish cooperativepartnerships with suppliers nutmeg and the need for financial aid from the government as theadditional capital for the business men to develop their business